(untitled) (Journal of Business and Technology (Dhaka), 2015)
The aim of this study is to find out the major challenges that hinder smooth operation of women entrepreneurs of Bangladesh. It also finds the reasons behind the success of the women entrepreneurship. Both primary and secondary data have been used to conduct the study. The questionnaire included questions about economic problems, family related issues, social constraints and other limitations faced by women entrepreneurs and the reasons behind their success. Women involved in various small and medium enterprises take on the challenge to work in a male-dominated society, competitive and complex economic and business environment. However, the identified challenges are inadequate capital, sales promotion, getting permission to start-up a business, gender discrimination, illiteracy and lack of knowledge among women, non-availability of training program and technical support, lack of managerial experience, in some cases young people make ill talk about the enterprise and so on. Personal qualities such as hard work and perseverance, management skills and marketing skills, support provided by their spouses or family are the main reasons behind the success of the women entrepreneurs. The level of participation of women in mainstream economic activities remains insufficient and the percentage of women in business is still much below than that of their male counterparts. Journal of Business and Technology (Dhaka) Vol.9(2) 2014; 27-41